Pengembangan UMKM Steak Ranjang - Agus Sutardi; Ahmad Hardiansyah; Bagas Syabani Sabrawera; Riyan Ismayadi; Siti Haniah (Master Manajemen, 2024)
The purpose of this research is to find out whether the Steak Ranjang business is worth it or not. This research uses descriptive qualitative research methods. The object of this research is the Steak Ranjang business, Jl A.H. Nasution No 59 branch. The results of this research are the Steak Ranjang business is feasible to run with several points of improvement for business development.